Nursing teacher training in active learning methodologies: ¿Is it necessary for knowledge? - Maricelys Jimenez Barrera; Jorge Luis Rodríguez Díaz; Jorge Leodan Cabrera Olvera (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Nursing teacher training is a professional challenge in a world characterized by globalization, accelerated development of science and technologies and complex processes of change that require new transformations of knowledge; an updating of the most advanced knowledge in active methodologies for nursing professors as a continuous and simultaneous process to promote multi-abilities and values is a must. Objective: To describe the main aspects that make up the Nursing teacher training process in active learning methodologies in higher education centers. Material and Methods: Descriptive study with an inductive content analysis.  A total of 76 bibliographies were examined in the Scopus, Scielo, and Eric databases, which were used as research sources. After applying the inclusion and exclusion criteria, the study was approached with a total of 27 articles. Conclusions: All professions and experiences will be affected in one way or another in this crucial advance, so the role of higher education centers is essential in the emerging implementation and teaching of active methodologies that today yearn to be applied in an unavoidable way in the different fields of knowledge.  The profession and Nursing science is not exempt from this trend and looks for a transforming process of competent professionals towards a competitive society of labor.